Mengintegrasikan Identitas Nasional Indonesia dalam Pendidikan Bahasa Inggris: Tantangan dan Strategi - Kholid, M. Ridho; Rahman, Bujang; Sinaga, Risma Margaretha (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research discusses the importance of maintaining Indonesian national identity in English language teaching and learning in the era of globalization. English as a global lingua franca is often considered to have the potential to erode local cultural values. Through a qualitative approach, this study analyzes the experiences and perceptions of 23 lecturers from the English Education Study Program of UIN Raden Intan Lampung. The findings show that the majority of lecturers emphasize the importance of integrating national identity into English education, despite facing challenges such as the dominance of Western perspectives in the curriculum and resistance to change. Proposed strategies include the use of local literature, project-based learning, as well as strengthening teacher training to support culturally responsive pedagogy. The research also highlights the role of technology as an innovative tool to connect students with their cultural heritage while improving English language skills. By identifying challenges and opportunities, the results of this study provide practical recommendations for creating a curriculum that strikes a balance between English proficiency and the preservation of Indonesia's national identity